PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TAI (TEAMS ASSISTED INDIVIDUALIZATION) TERHADAP SIKAP KERJASAMA DAN SIKAP BERTANGGUNG JAWAB SISWA - Ishak, Muchamad (STKIP Pasundan, 2015)
This study aims to reveal the effectiveness of the TAI type of cooperative learning model in enhancing students' attitude of cooperation and responsible attitude. The learning model emphasizes more on solving individual learning problems as a group's responsibility, so that the model is believed to improve cooperation and responsibility. The method used is an experimental method with a